THE IMPACT OF FUEL PRICE INCREASE ON STOCK PRICE IN INDONESIA STOCK EXCHANGE - Teddy Chandra (STIE Perbanas Surabaya, 2013)
The purpose of this research is to analyze the response ofIndonesian Capital Market to increasein fuel price as announced by the Government on June 22nd, 2013. This study uses abnormal returns and trading volume activity as the indicatorsto observe investors responses in the capitalmarket. Event study is used in order to examine investors responses. It measures the investorsresponse before and after the announcement of increase infuel price. The sample used in thisstudy includes all companies listed on the LQ-45 for the period of February to July 2013. Theresult indicates that there are significant negative abnormal returns before the announcement ofincreasing in fuel price and there are positive abnormal returns after the announcement of increasing in fuel price. However,there is no significant difference between the abnormal returnsbefore and after the announcement. Additionally, there is an increase in activity shown by theincrease in trading volume activity before and after the announcement. Yet, there is no significantdifference between the activity before and after the announcement.